Evaluation and implementation of clinical decision support tools for antimicrobial stewardship - (:unkn) unknown (My University, 2021)
Inappropriate prescription of antimicrobials impacts clinical outcomes and increases antimicrobial resistance. Antimicrobial stewardship interventions have been developed to improve the quality of antimicrobial prescribing. Among the interventions studied, decision supports tools, whether digital or in paper format, may help optimize antimicrobial prescribing. The objective of this work was to assess and extend the implementation and use of existing decision support tools for antimicrobial prescribing. Antibioclic is a free clinical decision support system (CDSS) for antimicrobial prescribing, targeting 37 common infectious diseases and used daily in primary care by more than 5,000 doctors in France. The first axis of the thesis work consisted of a qualitative study analysing the potential benefits and risks of the extension of Antibioclic in West Africa, as well as the obstacles and facilitators to its development, its adaptation and its implementation in this context. To this end, we organized a workshop in Burkina Faso in June 2019 which brought together 47 doctors representing 9 West African countries and 6 medical specialties. The participants considered that Antibioclic could improve patient care, encourage the development and updating of national antibiotic therapy recommendations and help develop capacities for the surveillance of infectious diseases in primary care. Participants stressed the need to adapt the tool to the local epidemiology of infectious diseases and antimicrobial resistance, and to include tuberculosis, HIV and malaria. The CDSS should be tailored to the availability of diagnostic tools and antibiotics in West Africa, as well as to the diversity of primary care structures in this region. The most frequently cited contextual barrier was the potential risk of increasing self-medication in West Africa. The second axis of this thesis aimed to study the role of community pharmacists in the management of urinary tract infections (UT
Keywords: African Research